Johnson's Canada East or Lower Canada and New Brunswick. - Johnson, A. J. (Alvin Jewett), 1827-1884 (A.J. Johnson, 1866)
Map shows late nineteenth century Canadian common roads, railroads, canals, counties, and cities, towns, and villages. Inset: "Vicinity of Montreal." Relief shown by hachures. Scale [ca. 1,960,000].